Modified Surgical Approach to Cervical Neurinomas with Intraforaminal Components: Minimal Invasive Facet Joint Sparing “Open-Tunnel” Technique - Banczerowski, Péter; Veres, Róbert; Vajda, János (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background The conventional posterior approaches, which may involve multilevel laminectomies and facetectomies, may lead to spinal deformities, instability, or subluxation. Our objective was to develop a minimally invasive approach suitable for exploring neuromas with an intraforaminal component in the cervical spine, with the aim of preserving mechanically relevant bone structures and the facet joints as much as possible.Methods The authors used the hemi-semi-laminectomy combined with partial lateral facetectomy “open-tunnel” technique in nine adult patients with neuromas of the cervical spine extending into the foramen.Results The operating field under the operating microscope was sufficient for tumor removal according to the keyhole concept. The approach did not affect the extent of tumor resection or neurological outcome. Complete removal was achieved in all patients, as confirmed by magnetic resonance imaging (MRI). The affected nerve roots included C3 in three cases, C2 and C4 in two, and C5 and C6 in one case. Average follow-up was 12 months, with a range from 8 to 18 months. Histological results were as follows: six schwannomas and three neurofibromas. Computed tomographic scans demonstrated the extension of the keyhole approaches and the moderately affected bony structures and facet joints. Instability was detected in none of the patients on the flexion or extension lateral radiographs during the follow-up period.Conclusion This modified surgical approach fulfills the requirements of other minimally invasive techniques and lowers the risk of damage to the crucial posterior stabilizers of the spine; furthermore, disintegration of vertebral arches and facet joints is reduced. The approach is suitable for exploring and removing neuromas located in the spinal canal and in the neuroforamen.
Keywords: keyhole; dumbbell tumor; intraforaminal; laminotomy; neuroma; surgical technique